2017
DOI: 10.1159/000454859
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Effects of Undernutrition and Placental Underperfusion in Fetal Growth Restriction Rabbit Models

Abstract: Introduction: Chronic reduction of oxygen and nutrient delivery to the fetus has been related to neurodevelopmental problems. Placental underperfusion induces a significant reduction in oxygen and nutrient delivery, whereas maternal undernutrition causes mainly nutrient deficiency. A comparison of the neurodevelopmental effects of both situations in pregnant rabbits was performed. Materials and Methods: The placental underperfusion model was induced after uteroplacental vessel ligation at 25 days of pregnancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 39 publications
(46 reference statements)
3
25
0
Order By: Relevance
“…MRI results support previous findings in the rabbit model showing impaired global network infrastructure, integration, and segregation evidenced by a reduction in FA-weighted strength as well as global and local efficiencies [13,28]. Likewise, alterations in brain networks have been previously described in humans to persist in childhood and early adolescence [11,12,14,36].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…MRI results support previous findings in the rabbit model showing impaired global network infrastructure, integration, and segregation evidenced by a reduction in FA-weighted strength as well as global and local efficiencies [13,28]. Likewise, alterations in brain networks have been previously described in humans to persist in childhood and early adolescence [11,12,14,36].…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, the rabbit brain shows a timing of perinatal brain white matter maturation closer to that of humans compared to other species [26]. Regarding the IUGR model, the perinatal results as well as the reported neonatal and long-term neurodevelopmental impairments are in good agreement with the literature for this model [13,24,28,29] and also with clinical observations [2][3][4][5][6]8]. Regarding histological assessment, DSs are plastic structures and are constantly subjected to external inputs [57].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Among the various particle types, we found airborne copper to be associated with tissue modifications and functional connectivity in the caudate nucleus in children . Other metals, such as iron, have been linked to structural changes in mice brain, and environmental Fe nanoparticles were found in brain tissue . Furthermore, two recent studies in rats exposed to NO 2 (an urban gas) reported clear evidence of brain damage, suggesting a specific neurotoxicity of NO 2 .…”
Section: Why To Investigate Air Pollution?mentioning
confidence: 71%
“…There were fractional anisotropy changes in multiple regions of the brain in 1 day‐old kits in response to uteroplacental insufficiency (Eixarch et al, ). Moreover, rabbits exposed to uteroplacental insufficiency displayed neurobehavioral alterations such as reduced exploratory activities/increased anxiety‐related behavior as adults (Batalle et al, ; Illa et al, ). The findings of impaired neurocognitive development and function in rabbit kits were in line with those of rat offspring that showed altered spatial memory, motor function, and sensorimotor gating function as a result of uteroplacental insufficiency during development (Lauritz, Siebel, Guille, Jefferies, & Wlodek, ).…”
Section: Models Of Iugr and Fetal Programmingmentioning
confidence: 99%